Review Over a 3-Year Period of European Union Proficiency Tests for Detection of Staphylococcal Enterotoxins in Food Matrices - Nia, Yacine (Toxins (Basel), 2016)
Staphylococcal food poisoning outbreaks are a major cause of foodborne illnesses in Europe and their notifications have been mandatory since 2005. Even though the European regulation on microbiological criteria for food defines a criterion on staphylococcal enterotoxin (SE) only in cheese and dairy products, European Food Safety Authority (EFSA) data reported that various types of food matrices are involved in staphylococcal food poisoning outbreaks. The European Screening Method (ESM) of European Union Reference Laboratory for Coagulase Positive Staphylococci (EURL CPS) was validated in 2011 for SE detection in food matrices and is currently the official method used for screening purposes in Europe. In this context, EURLCPS is annually organizing Inter-Laboratory Proficiency Testing Trials (ILPT) to evaluate the competency of the European countries’ National Reference Laboratories (NRLs) to analyse SE content in food matrices. A total of 31 NRLs representing 93% of European countries participated in these ILPTs. Eight food matrices were used for ILPT over the period 2013–2015, including cheese, freeze-dried cheese, tuna, mackerel, roasted chicken, ready-to-eat food, milk, and pastry. Food samples were spiked with four SE types (i.e., SEA, SEC, SED, and SEE) at various concentrations. Homogeneity and stability studies showed that ILPT samples were both homogeneous and stable. The analysis of results obtained by participants for a total of 155 blank and 620 contaminated samples allowed for evaluation of trueness (>98%) and specificity (100%) of ESM. Further to the validation study of ESM carried out in 2011, these three ILPTs allowed for the assessment of the proficiency of the NRL network and the performance of ESM on a large variety of food matrices and samples. The ILPT design presented here will be helpful for the organization of ILPT on SE detection by NRLs or other expert laboratories.